Effects of remote monitoring of patients with heart failure based on smartphone application in the context of the COVID-19 pandemic in the Kyrgyz Republic. (14th October 2021) - Rustambekova, A R; Djusupbekova, M R; Moldobaeva, A A; Moldomamatova, A I; Noruzbaeva, A M
Abstract: Background: Patients with CHF were the most vulnerable during the COVID-19 pandemic. Given to reduce hospitalizations and outpatient appointments, remote monitoring of CHF patients using a mobile application in response to the COVID-19 pandemic has proven particularly relevant, providing continuous specialized medical care and ensuring social distancing. Purpose: To study the clinical effectiveness of the implementation of a mobile application for remote monitoring of patients with CHF compared with standard practice during the COVID-19 pandemic in a mountainous country. Methods: ERICA-HF is a randomized, controlled, open-label study. Were included patients with verified CHF III FC (NYHA) with randomization to the main group of remote monitoring of patients using a mobile application + standard treatment (n=200) or to the control group on standard outpatient follow-up at the place of residence (n=100), for 12 months. The assessment of the clinical course of CHF is carried out on the basis of clinical indicators that allow assessing the current state of patients, depending on the quantitative assessment of deviations above or below the threshold values, consisting of seven points: shortness of breath, position in bed, heartbeating, edema, weight, blood pressure, heart rate, which the patient fills twice a week, with the possibility of automatically notifying the doctor and the patient. The application is equipped with two-way feedback in the form of structured telephone support and online chat. Quality of life assessment according to the Minnesota Living With Heart Failure Questionnaire, the ability to self-control according to the scale EHFScBS_9. The primary outcome is the percentage of unplanned rehospitalizations for HF decompensation, quality of life, mortality from CHF. The main secondary outcomes are cost-effectiveness and adherence to treatment. Results: During the COVID-19 pandemic, 209 patients on remote monitoring with CHF from all regions (63% men, age 65±11 years) were observed by coordinating cardiologists, 24 of them got sick with COVID-19, 7 received hospital treatment due to the development of HF decompensation, pneumonia and respiratory failure, 3 died of pneumonia. 9 participants dropped out of the study due to Internet traffic interruptions. 95% of patients noted high compliance, confidence, gave a positive assessment and use of the mobile application. Conclusion: Remote monitoring using a mobile application was an effective means of managing patients with CHF in socially isolation. This suggests that remote monitoring using a smart phone can be a good alternative to outpatient practice, which we have demonstrated in the context of the COVID-19 pandemic. Also, the relatively low cost can greatly facilitate the implementation of remote monitoring programs using a mobile application. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): National center of cardiology and internal medicine named after academician M. Mirrakhimov